Preliminary study of musculoskeletal complaints and ergonomic risk factors among catering workers - Ezrin Hani, Sukadarin; Junaidah, Zakaria (Environmental and Occupational Health Society Malaysia and Department of Environmental and Occupational Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Objective: A cross-sectional study was carried out to investigate the ergonomics risk factors, identify the symptom or significant factors of Work- Related Musculoskeletal Disorders (WMSDs) and to find the relationship between exposure of ergonomic risk score and musculoskeletal complaints among sixty catering workers (n=60) in a self-owned catering company inMalaysia.